A dictionary of oil & gas industry terms - Roberts, Peter (Lawyer) (Oxford University Press, 2023)
Roberts' dictionary is a comprehensive yet concise guide to the various legal, regulatory, technical, commercial, and financial abbreviations, acronyms, terms and phrases which define the oil and gas industry today. The dictionary is divided into three sections: commonly-used acronyms, an A to Z definition of terms and phrases and a series of technical appendices which summarise certain essential aspects of the industry.Written by a leading practitioner and containing over 7,000 definitions plus a series of technical and narrative appendices, this is an essential guide to interpreting the industry's extensive and complex jargon.--